ACCOUNTING AND ANALYTICAL SUPPORT OF ENTERPRISE MANAGEMENT IN DIGITAL ECONOMY - CHIZH, VERA; HAVRYLENKO, VALENTINA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Processes of globalization in the economy and the complex process of their development need the use of information technology. Therefore, attention should be paid to creating effective processes for the use of all technological opportunities for the business and society development. The article examines changes in accounting and analytical support of enterprise management under the influence of the information tools development. The stages of information technologies development in the accounting and analytical support of enterprise management are determined and their characteristics are given.  It is established that the newest innovative means of formation and processing of information is blockchain technology. It is noted that the digitization of the accounting system using blockchain technology will eliminate the need for separate accounting of transactions between companies and cross-checking, which often requires the use of external auditors. Approaches to the essence of this technology are systematized.  The components of technology are considered and its essence concerning application in accounting and analytical maintenance of enterprise management is defined. Emphasis is placed on the need to solve legal and personnel problems, to eliminate the inconsistency of training areas in accounting with the requirements of the modern digital economy.  It is noted that the use of digital economy tools, the rapid development of which we see today, creates new business opportunities and undeniable competitive advantages.  Subsystems of accounting and analytical maintenance of enterprise management with use of blockchain technology are offered. It is noted that the accounting field is quite conservative and requires a special approach to the use and implementation of blockchain technology.  Emphasis is placed on the need to solve legal and personnel problems, to eliminate the inconsistency of training areas in accounting with the requirements of the modern digital economy.
Keywords: accounting; management; automation; digital technologies; blockchain